2008
DOI: 10.1186/1471-2156-9-84
|View full text |Cite
|
Sign up to set email alerts
|

Association between fatty acid compositions and genotypes of FABP4 and LXR-alpha in Japanese Black cattle

Abstract: Background: Fatty acid composition has become an important trait in the beef industry in terms of beef flavor and decreasing the circulating concentration of LDL cholesterol. In this study, we examined the association between polymorphisms of six genes, adipocytes-type fatty acid binding

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
76
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 27 publications
3
76
5
Order By: Relevance
“…Interestingly, in the livestock field, it is known as a key candidate gene for meat marbling, which is a phenomenon quite similar to muscle fatty infiltration 30, 31. Genetic ablation and pharmacological inhibition studies have shown that FABP4 plays a critical role in many aspects of the development of metabolic diseases and have suggested FABP4 as a therapeutic target for such diseases 29, 32, 33, 34.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in the livestock field, it is known as a key candidate gene for meat marbling, which is a phenomenon quite similar to muscle fatty infiltration 30, 31. Genetic ablation and pharmacological inhibition studies have shown that FABP4 plays a critical role in many aspects of the development of metabolic diseases and have suggested FABP4 as a therapeutic target for such diseases 29, 32, 33, 34.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we investigated the single nucleotide polymorphisms (SNPs) of FABP4 gene (the 7516G>C SNP) and SCD gene (SNP 878T>C), which have been reported to have an effect on the fatty acid composition and content in beef and therefore influence its flavour and juiciness (Taniguchi et al 2004;Michal et al 2006;Hoashi et al 2008;Matsuhashi et al 2011). The purpose of this work was to evaluate the relationship between these genes and the FA content in Aberdeen Angus and Blonde d'Aquitaine breeds of beef cattle.…”
mentioning
confidence: 99%
“…The effects of four nonsynonymous substitutions in FABP4 and LXRα were investigated using a Japanese Black cattle population (Hoashi et al, 2008). The FABP4 I74V had a highly significant effect on the percentage of C16:1.…”
Section: Sterol Regulatory Element Binding Protein-1mentioning
confidence: 99%
“…We also surveyed additional genetic markers associated with fatty acid composition (Hoashi et al 2008). The fulllength CDS for six genes, adipocytes fatty acid binding protein (FABP4), liver X receptor α (LXRα), cytochrome b 5 , long-chain acyl-CoA synthetase (ACSL) 1, ACSL4, and diacylglycerol acyltransferase 2, were sequenced to identify polymorphisms in Japanese Black and Holstein cattle.…”
Section: Sterol Regulatory Element Binding Protein-1mentioning
confidence: 99%